O princípio da irredutibilidade do valor dos benefícios no regime geral de previdência social - Teles, Graciele Pinheiro (2008)
This study discusses the irreducibility principle of the value of social security benefits. The steep and long historical process of acknowledgement and spread of human rights ends up providing a constitutional status to them. Social rights are fundamental and require the State intervention to support individual and social needs. Social security is a basic right which aims at safeguarding the dignity of the human being. According to the Brazilian Federal Constitution, health and social welfare comprises the Social Security System which, in turn, settles social order. Thus, the aims of the Social Security System and those of the social order are the same. Social welfare and social justice are reached through the primacy of work. The general regulation of the Social Security System brings together workers of the private sector and excludes civil servants. To calculate and guarantee the benefits of any insured person, his monthly earnings must be subjected to the irreducibility principle. According to this principle, the benefit granted must assure that the insured keeps the buying power he had during his working years. The benefits are also subjected to a criterion of readjustment that preserves the value of money, as measured by the quantity and quality of products and services it can buy. Eligibility for benefits and their maintenance are two distinct and important stages for the insured. These two moments guarantee the pension and they are estimated in diverse ways. However, none of the benefits can have an amount below the minimum wage; actual earnings have to be incorporated; a minimum and maximum value must be fixed; monetary changes must be considered and an update of the value of contribution salary paid are used for estimating the benefits